On the elusive isotopic composition of lunar Pb - Nemchin, Alexander; Whitehouse, M.; Grange, Marion; Muhling, J. (Pergamon, 2011)
Highly radiogenic Pb isotope compositions determined for volcanic glass beads from the Apollo 14 soil sample 14163 are similar to those commonly determined for mare basalts and are correlated with chemical variations observed in the beads. This indicates that Pb unsupported by in-situ U decay has a similar origin in both glass beads and mare basalt samples and is likely to reflect variations of 238U/204Pb (µ) in the lunar mantle. An alternative explanation that this Pb is a result of late equilibration with the radiogenic Pb present in soil is less likely as it would imply that all other characteristics of glass beads such as their chemistry must also be a consequence of equilibration near the lunar surface. Regardless of the origin of unsupported Pb, observed variations of Pb isotope compositions in the glass beads and mare basalts appear to be a result of two component mixing between a primitive reservoir with a µ -value similar to the Earth’s mantle and KREEP with a µ-value in excess of several thousand. This range cannot be explained by the fractionation of major rock forming minerals from the crystallising Lunar Magma Ocean and instead requires substantial extraction of sulphide late in the crystallisation sequence. The proportion of sulphide required to produce the inferred range places limits on the starting l of the Moon prior to differentiation, demanding a relatively high value of about 100–200. Low µ indicated by several basalt samples and previously analysed volcanic glass beads can be explained by the preservation of an early (but post Ferroan Anorthosite) sulphide rich reservoir in the lunar mantle, while a complete range of Pb isotope compositions observed in the glass beads and mare basalts can be interpreted as mixing between this sulphide rich reservoir and KREEP.